Three-phase bidirectional electric vehicle charger for vehicle to grid operation and grid voltage regulation - Tan K.M.; Ramachandaramurthy V.K.; Yong J.Y. (Institute of Electrical and Electronics Engineers Inc., 2023)
DC-DC converters; Electric load flow; Electric machine control; Electric power system control; Electric power transmission networks; Electric rectifiers; Electric utilities; Electric vehicles; Power converters; Reactive power; Rectifying circuits; Vehicles; Voltage control; Voltage regulators; Battery chargers; Bidirectional power flow; Bidirectional vehicles; Dc link capacitor; Electric vehicle charging; Reactive power compensation; Regulation functions; Vehicle to grids; Charging (batteries)